2020
DOI: 10.1038/s41598-020-62135-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of diabetes and hyperglycaemia with intraocular pressure in a Japanese population: the JPHC-NEXT Eye Study

Abstract: Although a meta-analysis previously suggested a positive relationship between diabetes and intraocular pressure (IOP), the interrelationships among diabetes, IOP, and other ocular biometric parameters remain unclear. The present study investigated the relationships of diabetes, haemoglobin A1c (HbA1c), and serum glucose with IOP and ocular hypertension (IOP > 21 mmHg) in non-glaucomatous Japanese adults living in Chikusei City. Diabetes was defined as a self-reported history of diabetes, the use of antidiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
10
3
Order By: Relevance
“…The results of this study are not in line with research conducted by (Baisakhiya et al, 2017); (Pimentel et al, 2015); (Hanyuda et al, 2020) and (Rizka et al, 2020), who stated in their research that there was a significant influence between blood sugar levels with increased IOP. The study noted that blood sugar levels affected IOP in both DM and non-DM patients.…”
Section: Discussioncontrasting
confidence: 98%
“…The results of this study are not in line with research conducted by (Baisakhiya et al, 2017); (Pimentel et al, 2015); (Hanyuda et al, 2020) and (Rizka et al, 2020), who stated in their research that there was a significant influence between blood sugar levels with increased IOP. The study noted that blood sugar levels affected IOP in both DM and non-DM patients.…”
Section: Discussioncontrasting
confidence: 98%
“…Several antidiabetic compounds have shown potential for glaucoma treatment (Lin et al, 2015;Maleškić et al, 2017;Sterling et al, 2021) (Table 3). In support of this, several studies have suggested that diabetes mellitus is a risk factor for glaucoma (Oshitari et al, 2007;Chopra et al, 2008;Welinder et al, 2009;Zhou et al, 2014;Horwitz et al, 2016;Jung et al, 2018;Hanyuda et al, 2020). Thus, it raises the question of whether glaucoma may be associated with retinal insulin desensitization (Agostinone et al, 2018) as well as insulin desensitization of the brain as associated with Alzheimer's and Parkinson's disease (Faiq et al, 2014;Dada, 2017;Faiq and Dada, 2017).…”
Section: Glucagon-like Peptide 1 Agonists and Other Antidiabetic Agen...mentioning
confidence: 97%
“…Storr-Paulsen et al 3 Schultz et al 37 Busted et al 15 Keoleian et al 38 Olsen et al 16 Inoue et al 39 Larsson et al 17 Sudhir et al 40 McNamara et al 14 Ziadi et al 41 Roszkowska et al 18 Sonmez et al 42 Rosenberg et al 19 Wiemer et al 43 Lee et al 20 Beato et al 47 Su et al 21 Wang et al 54 Oriowo et al 22 Xiao et al 55 Modis et al 23 Wang et al 57 Ozdamar et al 24 Calvo-Maroto et al 25 Briggs et al 26 Sanchis-Gimeno et al 27 Altay et al 30 Kumar et al 44 Jeziorny et al 45 Luo et al 46 Ramm et al 48 Çolak et al 49 Hanyuda et al 50 Taşlı et al 51 Srećković et al 52 Suraida et al 53 Deák et al 56 Kim and Kim 58 CCT, central corneal thickness.…”
Section: Increase In Cct Values No Increase In Cct Valuesmentioning
confidence: 99%